Evaluation of Website Performance and Usability Using GTMetrix, Usability Testing, and System Usability Scale (SUS) Methods - Toto Andri Puspito (JURNAL TEKNIK INFORMATIKA, 2024)
This study was conducted to measure the performance of IAIN Metro's website in terms of performance and user perception to ensure that the campus website can adequately support visitors' needs. This study aims to determine things that need to be improved to improve the performance of the IAIN Metro website. To get comprehensive results from the performance of the website, this research uses GTMetrix to analyse the technical performance of the IAIN Metro website, and then, to test user perceptions, researchers use Usability Testing and System Usability Scale methods. In usability testing, several aspects will be measured to determine usability problems, namely learnability and efficiency, while the System Usability Scale questionnaire will be used to test the satisfaction level. Based on the test results using GTMetrix, after testing, several aspects of the access speed of the IAIN Metro website need to be improved. Although, in general, from the test results, Usability Testing and System Usability Scale users still consider the performance of the website to be acceptable, the results of the first task on Time Based Efficiency testing show that initial access to the main page metrouniv.ac.id, takes a relatively long time compared to other tasks. This is also evident from the GTMetrix score on the performance aspect, which has a low presentation of 25%. Therefore, optimisation is needed on the main page to improve website performance.